(untitled) (Scientific journal of the Fergana State University, 2024)
The youth, who make up the bulk of the population, the issue of ensuring the psychological health of future specialists was studied on the example of future teachers. The article also highlights the current state of public health in the world and in our country. In the course of this study, we conducted a “questionnaire” among graduate students of the pedagogical field in order to determine the level of acceptance as a tool for self-realization, development in the chosen professional activity, a place in a new team, awareness of their identity and assessment of the importance of membership in it. Among the factors influencing the psychological health of future teachers, the influence of professional motivation has been studied. It is based on the methodological and methodological aspects of research work.